Discarded species in artisanal fisheries South Sumatra, Indonesia : case study on crab gill nets - Fauziyah; Wike Ayu Eka Putri; Desi Arianti; Agustriani, Fitri; Rozirwan; Ellis Nurjuliasti Ningsih; Purwiyanto, Anna Ida Sunaryo (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study identified the discard species generated by the crab gillnet for targeting the blue swimming crab Portunus pelagicus (Linnaeus 1758) in the Banyuasin estuarine of South Sumatra, Indonesia. The fishing gear yielded the discarded catch about 12% (25.68 kg) of the total catch in weight (212.68 kg). For the discarded catch, 703 individuals represented 18 species from 3 phyla (Arthropoda, Chordata, and Mollusca). The crustaceans Charybdis helleri (Milne-Edwards 1867), Clibanarius spp., Matuta planipes (Fabricius 1798), and Libinia dubia (Milne Edwards 1834) were the majority components of these discards accounted for 90% of the total discards. Results of ecological classification rare, i.e., Chiloscyllium indicum (Gmelin 1789), and occasional, i.e., Chiloscyllium punctatum (Müller & Henle 1838), and Maculabatis macrura (Bleeker 1852) included in the International Union for Conservation of Nature (IUCN) red list as Vulnerable (C. indicum), Near Threatened (C. punctatum), and Endangered (M. macrura) category. Based on the IUCN status, two species of crustaceans i.e., Carcinoscorpius rotundicauda (Latreille 1802) and Tachypleus gigas (Müller 1785) listed as ‘Data Deficient’. Discarded on crab gillnet fishing in Banyuasin waters is a challenge for species that need to be conserved (shark, ray, and horseshoe crabs). Species with IUCN red list status ranging from Data Deficient to Endangered were found dead, except for horseshoe crabs. Mitigation options offered include captive breeding of horseshoe crabs, the release of protected species when caught, and fishing gear modification. These findings can help design suitable mitigations for discarding crab gill nets.